Identifying Leukemia-associated Immunophenotypes in Acute Myeloid Leukemia Patients Using Multiparameter Flow Cytometry - Hadeer Mohamed Rasheed; Hanaa Mahmoud Donia; Eman Attia Nadwan; Zeinab Ibrahim Mourad; Nahla Farahat (Oman Medical Journal, 2021)
Objectives: We sought to identify leukemia-associated immunophenotypes (LAIPs) in 50 acute myeloid leukemia (AML) patients at diagnosis using an eight-color multiparameter flow cytometry (MFC) panel and to detect if they showed any alteration in relapsed/refractory cases. Methods: We used the eight-color MFC panel with CD45/side scatter log gating strategy to analyze LAIPs in 50 AML patients presenting to Alexandria University Hospitals, Egypt at diagnosis and relapse and refractory cases. Twenty age and sex matched bone marrow samples from patients performing bone marrow aspirate for non-malignant hematological indications were included as controls. Results: LAIPs were observed in 43 (86.0%) cases. Only one aberrant immunophenotype was identified in four cases (9.3%), while two to 12 aberrant immunophenotypes were found in the other 39 (90.7%) cases. Strong LAIPs were obtained by combining CD2, CD4, CD56, with either CD34 or CD117, in contrast to CD19, which has to be combined with CD117. Refractory cases showed the presence of the same LAIPs at both initial diagnosis and persistent disease. One case showed the acquisition of new LAIPs after relapse. Conclusions: The good choice of LAIPs depends on their specificity rather than their frequency. The results of this study can help in increasing the sensitivity of LAIPs strategy in minimal residual disease using MFC in AML patients, which is considered an important post-diagnosis parameter associated with prognosis and clinical outcome.